Preparation method of barium titanate ceramic materials with different grain sizes to improve flexoelectric response performance
The grain size and polarized surface layer of barium titanate ceramics are regulated through two-step sintering method and heat treatment process, which significantly improves its flexural electrical response performance, and solves the shortcomings of barium titanate ceramics in the prior art. , realizes the preparation of high-performance ceramics.
Patent Information
- Application Number
- CN202310550461.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-16
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-05-16
AI Technical Summary
In the prior art, there is a lack of effective methods for regulating the flexural electrical response performance of barium titanate ceramics, and the impact of grain size on its electrical properties has not been fully studied.
A two-step sintering method is used to prepare barium titanate ceramics of different grain sizes, and a polarized surface layer is formed through a heat treatment process to regulate its flexural electrical response performance. Specific steps include preparing the blank for use, sintering and heat treatment, adjusting the temperature and cooling rate to control the grain size and relative density, and forming a high density ceramic.
By changing the grain size and heat treatment method, the flexural electrical coefficient of barium titanate ceramics is greatly improved, and the flexural electrical coefficient of coarse crystal ceramics can be increased by more than 10 times compared with fine crystal ceramics. The prepared ceramics have high relative density and excellent physics performance.
Smart Images

Figure CN116573931B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of functional materials, and in particular relates to a method for regulating the flexoelectric response of barium titanate (BaTiO3) ceramics by changing their grain size. Background Art
[0002] The flexoelectric effect describes the interaction between dielectric polarization and strain gradient. Unlike the piezoelectric effect, the flexoelectric effect is not limited by the symmetry of the material. It is a ubiquitous electromechanical coupling effect in solid dielectrics and can be widely used in fields such as sensors and actuators. The magnitude of the flexoelectric effect is expressed by the flexoelectric coefficient (μ ijkl ) or flexural coupling coefficient (f ijkl ) is used to characterize the simple low dielectric constant dielectric μ ijkl Theoretically, the order of magnitude is 10 -11 -10 -10 C / m. It was not until the beginning of the 21st century that researchers discovered that ferroelectric ceramics have large flexoelectric coefficients, which are several orders of magnitude larger than the theoretical value. They have broad application prospects in practical applications and have attracted the interest of many researchers. In recent years, the mechanism of the large deviation between the measured values and the theoretical calculated values of the flexoelectric response of ferroelectric oxides has been studied. For example, the abnormally large flexoelectric coefficient of ferroelectric ceramics mainly comes from the spontaneously polarized surface layer, the formation of which is a stress-related phenomenon (Phys Rev Lett, 2018, 121(5): 057602). When barium titanate ceramics are heat treated at a temperature higher than the Curie temperature (200 °C), a phase transition will occur when the ceramics are cooled from high temperature. The grains of the bulk phase are bound by the surrounding grains, and the residual stress generated cannot be released. The grains of the surface layer are free in the direction perpendicular to the surface, and the stress in this direction can be released to form a spontaneously polarized surface layer. This spontaneously polarized surface layer is the main source of the large flexoelectric effect of ferroelectric ceramics.
[0003] Barium titanate ceramics are considered to be one of the earliest ferroelectric and piezoelectric ceramics widely used in capacitors, sensors and brakes. Grain size (GS) has an important influence on the electrical properties of ferroelectric ceramics, such as dielectric constant and piezoelectric coefficient. When the grain size is about 1 μm, barium titanate can obtain the maximum dielectric and piezoelectric response, which may be because domain wall motion is easier at medium grain size. In addition, the ferroelectric properties of barium titanate ceramics are also related to grain size. However, there are few studies on the effect of grain size on the flexoelectric effect of barium titanate ceramics. Summary of the invention
[0004] In order to achieve the regulation of the flexoelectric response performance of barium titanate ceramics, the present invention provides a method for preparing barium titanate ceramic materials with different grain sizes for improving the flexoelectric response performance.
[0005] The present invention adopts a two-step sintering method to prepare barium titanate ceramics with different grain sizes, thereby regulating the flexoelectric response of the barium titanate ceramics, and through a heat treatment process, the barium titanate ceramics with large grain sizes form a polarized surface layer, thereby greatly improving its flexoelectric coefficient.
[0006] The preparation steps of a barium titanate ceramic material with different grain sizes to improve flexoelectric response performance are as follows:
[0007] (1) Preparation of green body
[0008] The barium titanate powder is granulated and dried to obtain a dried granulated powder; the dried granulated powder and a polyvinyl alcohol solution with a mass concentration of 5 wt% are mixed evenly at a mass ratio of 10:1, and uniaxially pressed into a green body in a mold; the green body is placed in a muffle furnace for heat preservation and firing to obtain a green body to be used;
[0009] The thickness of the blank to be used is 0.8 to 1 mm;
[0010] (2) First step: sintering
[0011] The blank to be used is placed in a muffle furnace, first heated to temperature T1 at a heating rate of 4 °C / min, and kept at this temperature for 1 min;
[0012] The temperature T1 is 1200°C-1400°C;
[0013] (3) Second step: sintering
[0014] Rapidly cool to temperature T2 at a rate of 50 °C / min, keep at this temperature for 20 h, and cool to room temperature along with the furnace to obtain barium titanate ceramic materials with different grain sizes;
[0015] The temperature T2 is 800°C-1200°C;
[0016] (4) Heat treatment
[0017] The barium titanate ceramic material was ground to a thickness of 0.5 mm, placed in a muffle furnace and heated to 200 °C at a heating rate of 3 °C / min, kept warm for 30 min, cooled with the furnace or taken out and quenched in ice silicone oil to obtain the heat-treated barium titanate ceramic material.
[0018] In the barium titanate ceramic material, the fine grain size is 0.59-0.97 μm, and the coarse grain size is 1.96-8.90 μm.
[0019] The technical solution is further defined as follows:
[0020] In the piezoelectric ceramic device prepared by using the barium titanate ceramic material, after heat treatment and slow cooling, a polarized surface layer is formed due to stress release, and the flexoelectric coefficient of the coarse-grained ceramic is 340 μC / m, which is more than 10 times higher than that of the fine-grained ceramic.
[0021] The beneficial technical effects of the present invention are embodied in the following aspects:
[0022] 1. Flexoelectric response is different from piezoelectric properties and dielectric properties. It is another physical property. Its generation mechanism is completely different from the other two properties. However, our research found that the flexoelectric response of barium titanate ceramics can also be regulated by changing the grain size. Compared with regulating the flexoelectric response of barium titanate ceramics by adjusting the dielectric constant or reducing the size of the ceramics, the method of regulating the flexoelectric response by grain size is simple to operate, has a wide range of applications, and does not damage other properties of the material. The flexoelectric response of barium titanate ceramics increases with the increase of grain size. When the grain size of barium titanate ceramics increases from 0.59μm to 8.90μm, the flexoelectric coefficient increases from less than 30 μC / m to 340 μC / m. In addition, coarse-grained and fine-grained barium titanate ceramics have different domain structures. Fine-grained ceramics have two-dimensional layered domains, while coarse-grained ceramics have three-dimensional banded domains. The two have differences in stress release behavior, which affects the formation of the polarized surface layer of barium titanate ceramics, thus having an important influence on the flexoelectric response of barium titanate ceramics. By slowly cooling barium titanate ceramics after heat treatment at 200 °C, the stress generated by the phase change experienced by the ceramics and the constraints of adjacent grains in the ceramics can be released through three-dimensional domains to form a spontaneously polarized surface layer. Therefore, the flexoelectric coefficient of coarse-grained ceramics can be greatly improved after heat treatment and slow cooling. The flexoelectric response of coarse-grained ceramics can be increased by more than 10 times compared with fine-grained ceramics, and the main reason for this is the surface layer.
[0023] 2. Unlike spark plasma sintering and microwave sintering, which produce a large number of pores and defects during the ceramic preparation process, the present invention adopts a two-step sintering method to prepare high-performance fine-grained barium titanate ceramics. The two-step sintering method consists of two steps. First, the sample is heated to a higher temperature to obtain a relative density of more than 75%, and then it is quickly cooled and maintained at a low temperature for a long time to obtain a high-density ceramic, and the grain size can be controlled by adjusting the first and second sintering temperatures. The relative density of the barium titanate ceramics prepared by the two-step sintering method in the present invention is greater than 90%, especially for barium titanate ceramics with a grain size of more than 0.69μm, the relative density is greater than 98%, and the prepared ceramics are fine and dense, and the sample quality is high. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Microstructure diagram of barium titanate ceramics with different grain sizes.
[0025] Figure 2XRD spectra of barium titanate ceramics with different grain sizes.
[0026] Figure 3 is the flexoelectric coefficient μ of barium titanate ceramics with different grain sizes after grinding, slow cooling and rapid cooling at room temperature ρ picture. DETAILED DESCRIPTION
[0027] The present invention will be further described in detail below in conjunction with specific embodiments and accompanying drawings.
[0028] The materials used in the following examples are described as follows: barium titanate powder with a purity of ≥99.9% and a fineness of 100 nm was purchased from Shandong Guoci Functional Materials Co., Ltd.
[0029] Example 1
[0030] The preparation steps of a barium titanate ceramic material with different grain sizes to improve flexoelectric response performance are as follows:
[0031] (1) Preparation of green body
[0032] The barium titanate powder is granulated and dried to obtain a dried granulated powder. The dried granulated powder and the polyvinyl alcohol solution with a mass concentration of 5 wt% are mixed evenly at a mass ratio of 10:1. Then the powder is poured into a 50 mm diameter mold, and a pressure of 20 MPa is applied on the tablet press, and the pressure is maintained for 5 min to fully mix the binder and the powder. Then the powder is continued to be ground in a mortar so that its particle size can pass through an 80 mesh sieve. The granulated powder needs to be baked in an oven at 120 °C for 2 h and uniaxially pressed into a disc with a 12.5 mm diameter mold. Put it in a muffle furnace and keep it at 800 °C for 2 h to remove the binder in the green body and obtain a green body to be used. The thickness of the green body to be used is 0.8 mm.
[0033] (2) First step: sintering
[0034] The finished green body was placed in a muffle furnace and first heated to 1200 °C at a heating rate of 4 °C / min and kept at that temperature for 1 min.
[0035] (3) Second step: sintering
[0036] See also Figure 1 (a) in the figure, and then rapidly cooled to 800 °C at a rate of 50 °C / min and kept at this temperature for 20 h, and then cooled in the furnace to obtain barium titanate ceramic materials with different grain sizes. The average grain size of the barium titanate ceramic material observed by SEM is 0.59 μm.
[0037] (4) Heat treatment
[0038] The barium titanate ceramic material was ground to a thickness of 0.5 mm, placed in a muffle furnace and heated to 200 °C at a heating rate of 3 °C / min, kept warm for 30 min, and cooled with the furnace to obtain the barium titanate ceramic material after heat treatment and slow cooling.
[0039] Au electrodes were plated on both sides of the barium titanate ceramic material, and its flexoelectric coefficient was measured to be 28 μC / m.
[0040] Example 2
[0041] The preparation steps of a barium titanate ceramic material with different grain sizes to improve flexoelectric response performance are as follows:
[0042] (1) Same as step (1) of Example 1.
[0043] (2) First step: sintering
[0044] The finished green body was placed in a muffle furnace, and the sample was first heated to 1200 °C at a heating rate of 4 °C / min and kept at that temperature for 1 min.
[0045] (3) Second step: sintering
[0046] See also Figure 1 (b) in the figure, and then rapidly cooled to 900 °C at a rate of 50 °C / min and kept at this temperature for 20 h, and then cooled in the furnace to obtain barium titanate ceramic materials with different grain sizes. The average grain size of the barium titanate ceramic material observed by SEM is 0.69 μm.
[0047] (4) Heat treatment
[0048] The barium titanate ceramic material was ground to a thickness of 0.5 mm, placed in a muffle furnace and heated to 200 °C at a heating rate of 3 °C / min, kept warm for 30 min, and cooled with the furnace to obtain the barium titanate ceramic material after heat treatment and slow cooling.
[0049] Au electrodes were plated on both sides of the barium titanate ceramic material, and its flexoelectric coefficient was measured to be 29 μC / m.
[0050] Example 3
[0051] The preparation steps of a barium titanate ceramic material with different grain sizes to improve flexoelectric response performance are as follows:
[0052] (1) Same as step (1) of Example 1.
[0053] (2) First step: sintering
[0054] The finished ceramic body was placed in a muffle furnace, and the sample was first heated to 1200 °C at a heating rate of 4 °C / min and kept at that temperature for 1 min.
[0055] (3) Second step: sintering
[0056] Then, the sample was rapidly cooled to 1000 °C at a rate of 50 °C / min and kept at this temperature for 20 h. The sample was then cooled in the furnace to obtain barium titanate ceramic materials with different grain sizes. The average grain size of the barium titanate ceramic material was 0.62 μm as observed by SEM.
[0057] (4) Heat treatment
[0058] The barium titanate ceramic material was ground to a thickness of 0.5 mm, placed in a muffle furnace and heated to 200 °C at a heating rate of 3 °C / min, kept warm for 30 min, and cooled with the furnace to obtain the barium titanate ceramic material after heat treatment and slow cooling.
[0059] Au electrodes were plated on both sides of the barium titanate ceramic material, and its flexoelectric coefficient was measured to be 33 μC / m.
[0060] Example 4
[0061] The preparation steps of a barium titanate ceramic material with different grain sizes to improve flexoelectric response performance are as follows:
[0062] (1) Same as step (1) of Example 1.
[0063] (2) First step: sintering
[0064] The finished ceramic body was placed in a muffle furnace, and the sample was first heated to 1250 °C at a heating rate of 4 °C / min and kept at this temperature for 1 min.
[0065] (3) Second step: sintering
[0066] See also Figure 1 (c) in the figure, and then rapidly cooled to 800 °C at a rate of 50 °C / min and kept at this temperature for 20 h, and then cooled in the furnace to obtain barium titanate ceramic materials with different grain sizes. The average grain size of the barium titanate ceramic material observed by SEM is 0.80 μm.
[0067] (4) Heat treatment
[0068] The barium titanate ceramic material was ground to a thickness of 0.5 mm, placed in a muffle furnace and heated to 200 °C at a heating rate of 3 °C / min, kept warm for 30 min, and cooled with the furnace to obtain the barium titanate ceramic material after heat treatment and slow cooling.
[0069] Au electrodes were plated on both sides of the barium titanate ceramic material, and its flexoelectric coefficient was measured to be 43 μC / m.
[0070] Example 5
[0071] The preparation steps of a barium titanate ceramic material with different grain sizes to improve flexoelectric response performance are as follows:
[0072] (1) Same as step (1) of Example 1.
[0073] (2) First step: sintering
[0074] The finished ceramic body was placed in a muffle furnace, and the sample was first heated to 1250 °C at a heating rate of 4 °C / min and kept at this temperature for 1 min.
[0075] (3) Second step: sintering
[0076] See also Figure 1 (d) in the figure, and then rapidly cooled to 900 °C at a rate of 50 °C / min and kept at this temperature for 20 h, and then cooled in the furnace to obtain barium titanate ceramic materials with different grain sizes. The average grain size of the barium titanate ceramic material observed by SEM is 0.97 μm.
[0077] (4) Heat treatment
[0078] The barium titanate ceramic material was ground to a thickness of 0.5 mm, placed in a muffle furnace and heated to 200 °C at a heating rate of 3 °C / min, kept warm for 30 min, and cooled with the furnace to obtain the barium titanate ceramic material after heat treatment and slow cooling.
[0079] Au electrodes were plated on both sides of the barium titanate ceramic material, and its flexoelectric coefficient was measured to be 58 μC / m.
[0080] Example 6
[0081] The preparation steps of a barium titanate ceramic material with different grain sizes to improve flexoelectric response performance are as follows:
[0082] (1) Same as step (1) of Example 1.
[0083] (2) First step: sintering
[0084] The finished ceramic body was placed in a muffle furnace, and the sample was first heated to 1300 °C at a heating rate of 4 °C / min and kept at that temperature for 1 min.
[0085] (3) Second step: sintering
[0086] Then, the sample was rapidly cooled to 1100 °C at a rate of 50 °C / min and kept at this temperature for 20 h. The sample was then cooled in the furnace to obtain barium titanate ceramic materials with different grain sizes. The average grain size of the barium titanate ceramic material was 1.96 μm as observed by SEM.
[0087] (4) Heat treatment
[0088] The barium titanate ceramic material was ground to a thickness of 0.5 mm, placed in a muffle furnace and heated to 200 °C at a heating rate of 3 °C / min, kept warm for 30 min, and cooled with the furnace to obtain the barium titanate ceramic material after heat treatment and slow cooling.
[0089] Au electrodes were plated on both sides of the barium titanate ceramic material, and its flexoelectric coefficient was measured to be 60 μC / m.
[0090] Example 7
[0091] The preparation steps of a barium titanate ceramic material with different grain sizes to improve flexoelectric response performance are as follows:
[0092] (1) Same as step (1) of Example 1.
[0093] (2) First step: sintering
[0094] The finished ceramic body was placed in a muffle furnace, and the sample was first heated to 1350 °C at a heating rate of 4 °C / min and kept at that temperature for 1 min.
[0095] (3) Second step: sintering
[0096] See also Figure 1 (e) in the figure, and then rapidly cooled to 1100 °C at a rate of 50 °C / min and kept at this temperature for 20 h, and then cooled in the furnace to obtain barium titanate ceramic materials with different grain sizes. The average grain size of the barium titanate ceramic material observed by SEM is 2.73 μm.
[0097] (4) Heat treatment
[0098] The barium titanate ceramic material was ground to a thickness of 0.5 mm, placed in a muffle furnace and heated to 200 °C at a heating rate of 3 °C / min, kept warm for 30 min, and cooled with the furnace to obtain the barium titanate ceramic material after heat treatment and slow cooling.
[0099] Au electrodes were plated on both sides of the barium titanate ceramic material, and its flexoelectric coefficient was measured to be 145 μC / m.
[0100] Example 8
[0101] The preparation steps of a barium titanate ceramic material with different grain sizes to improve flexoelectric response performance are as follows:
[0102] (1) Same as step (1) of Example 1.
[0103] (2) First step: sintering
[0104] The finished ceramic body was placed in a muffle furnace, and the sample was first heated to 1400 °C at a heating rate of 4 °C / min and kept at that temperature for 1 min.
[0105] (3) Second step: sintering
[0106] Then, the sample was rapidly cooled to 1100 °C at a rate of 50 °C / min and kept at this temperature for 20 h. The sample was then cooled in the furnace to obtain barium titanate ceramic materials with different grain sizes. The average grain size of the barium titanate ceramic material was 8.30 μm as observed by SEM.
[0107] (4) Heat treatment
[0108] The barium titanate ceramic material was ground to a thickness of 0.5 mm, placed in a muffle furnace and heated to 200 °C at a heating rate of 3 °C / min, kept warm for 30 min, and cooled with the furnace to obtain the barium titanate ceramic material after heat treatment and slow cooling.
[0109] Au electrodes were plated on both sides of the barium titanate ceramic material, and its flexoelectric coefficient was measured to be 223 μC / m.
[0110] Example 9
[0111] The preparation steps of a barium titanate ceramic material with different grain sizes to improve flexoelectric response performance are as follows:
[0112] (1) Same as step (1) of Example 1.
[0113] (2) First step: sintering
[0114] The finished ceramic body was placed in a muffle furnace, and the sample was first heated to 1400 °C at a heating rate of 4 °C / min and kept at that temperature for 1 min.
[0115] (3) Second step: sintering
[0116] See also Figure 1 (f) in the figure, and then rapidly cooled to 1200 °C at a rate of 50 °C / min and kept at this temperature for 20 h, and then cooled in the furnace to obtain barium titanate ceramic materials with different grain sizes. The average grain size of the barium titanate ceramic material observed by SEM is 8.90 μm.
[0117] (4) Heat treatment
[0118] The barium titanate ceramic material was ground to a thickness of 0.5 mm, placed in a muffle furnace and heated to 200 °C at a heating rate of 3 °C / min, kept warm for 30 min, and cooled with the furnace to obtain the barium titanate ceramic material after heat treatment and slow cooling.
[0119] Au electrodes were plated on both sides of the barium titanate ceramic material, and its flexoelectric coefficient was measured to be 340 μC / m.
[0120] Figure 1 The SEM images of Example 1, Example 2, Example 4, Example 5, Example 7 and Example 9 show that BTO ceramics with a grain size of 0.59-8.90 μm were successfully prepared, and the grain size distribution was uniform. Figure 2 It can be seen that all samples have a tetragonal perovskite structure and no second phase is produced.
[0121] Table 1 Flexoelectric coefficient μ of ceramic samples of Examples 1-9 after heat treatment and slow cooling ρ .
[0122] GS(μm) 0.59 0.62 0.69 0.80 0.97 1.96 2.73 8.30 8.90 <![CDATA[μ ρ (μC / m)]]> 28 33 29 43 58 60 145 223 340
[0123] As shown in Table 1 and Figure 3 As shown in the figure, when GS>2.73 μm, slow cooling after heat treatment can further increase the flexoelectric coefficient of coarse-grained samples, especially for ceramics with a grain size of 8.90 μm, the flexoelectric coefficient can reach 340 μC / m. This is due to the different domain structures of coarse-grained and fine-grained ceramics, and there are differences in stress release behavior. The formation of domains is the result of energy minimization to reduce the mechanical stress generated during the phase change. For fine-grained barium titanate ceramics, the deformed grains can be energy-adjusted in two dimensions through simple lamellar domains, while in coarse-grained barium titanate ceramics, grains with more complex herringbone band domains can release stress in three dimensions for energy adjustment. The stress generated by the phase change of ceramics during slow cooling at high temperatures and the constraints of adjacent grains in the ceramics can be released through three-dimensional domains to form a spontaneously polarized surface, which is the main source of the larger flexoelectric response of coarse-grained barium titanate ceramics. However, the flexoelectric coefficient of fine-grained ceramics decreased after heat treatment, and it is speculated that the formation of two-dimensional lamellar domains cannot fully release stress and changes the polarized surface layer.
[0124] Examples 10-18
[0125] Different from Example 1-9, the barium titanate ceramic sample after heat treatment and slow cooling in Example 1-9 was polished off by 20 μm on both sides to obtain polished barium titanate ceramic, and Au electrodes were plated on both sides of the sample to measure its flexoelectric coefficient.
[0126] Table 2 Flexoelectric coefficient μ of polished ceramic samples of Examples 10-18 ρ .
[0127] GS(μm) 0.59 0.62 0.69 0.80 0.97 1.96 2.73 8.30 8.90 <![CDATA[μ ρ (μC / m)]]> 14 21 7 91 115 133 148 118 174
[0128] From Table 2 and Figure 3 It can be seen that the flexoelectric coefficient of the coarse-grained sample decreases due to the removal of the polarized surface layer of the sample by grinding.
[0129] Examples 19-27
[0130] Different from Examples 1-9, during the heat treatment process in step (4), the barium titanate ceramic sample is polished to a thickness of 0.5 mm and then placed in a muffle furnace. The sample is heated to 200 °C at a heating rate of 3 °C / min and kept warm for 30 min. The sample is then immediately placed in ice silicone oil to obtain a heat-treated and rapidly cooled sample. Au electrodes are plated on both sides of the sample to measure its flexoelectric coefficient.
[0131] Table 3 Flexoelectric coefficient μ of ceramic samples of Examples 19-27 after heat treatment and rapid cooling ρ .
[0132] GS(μm) 0.59 0.62 0.69 0.80 0.97 1.96 2.73 8.30 8.90 <![CDATA[μ ρ (μC / m)]]> 38 29 28 62 96 86 51 65 163
[0133] As shown in Table 3 and Figure 3 As shown in the figure, rapid cooling makes it impossible to release the stress on the surface layer of the sample in time and the polarized surface layer cannot be formed. Therefore, for barium titanate ceramics with GS ≥ 0.80 μm, their flexoelectric coefficients are reduced compared with those of samples after heat treatment and slow cooling.
[0134] It will be easily understood by those skilled in the art that the above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing barium titanate ceramic materials with different grain sizes for improving flexoelectric response performance, characterized in that: The steps are as follows: (1) Preparation of green body The barium titanate powder is granulated and dried to obtain a dried granulated powder; the dried granulated powder and a polyvinyl alcohol solution with a mass concentration of 5 wt% are mixed evenly at a mass ratio of 10:1, and uniaxially pressed into a green body in a mold; the green body is placed in a muffle furnace for heat preservation and firing to obtain a green body to be used; The thickness of the blank to be used is 0.8 to 1 mm; The purity of barium titanate powder is ≥99.9% and the fineness is 100 nm; (2) First step: sintering The blank to be used is placed in a muffle furnace, first heated to temperature T1 at a heating rate of 4°C / min, and kept at this temperature for 1 min; The temperature T1 is 1200° C.-1400° C.; (3) Second step: sintering Rapidly cool to temperature T2 at a rate of 50°C / min, keep at this temperature for 20 h, and cool to room temperature along with the furnace to obtain barium titanate ceramic materials with different grain sizes; The temperature T2 is 800°C-1200°C; (4) Heat treatment The barium titanate ceramic material was ground to a thickness of 0.5 mm, placed in a muffle furnace, heated to 200°C at a heating rate of 3°C / min, kept at that temperature for 30 min, and cooled with the furnace to obtain the barium titanate ceramic material after heat treatment and slow cooling; In the barium titanate ceramic material, the fine grain size is 0.59-0.97 μm, and the coarse grain size is 1.96-8.90 μm.
2. A method for preparing barium titanate ceramic materials with different grain sizes that improve flexoelectric response performance according to claim 1, characterized in that: In the piezoelectric ceramic device prepared by using the barium titanate ceramic material after the heat treatment and slow cooling, due to the formation of a polarized surface layer due to stress release, the flexoelectric coefficient of the coarse-grained ceramic is 340 μC / m, which is more than 10 times higher than that of the fine-grained ceramic.
Citation Information
Patent Citations
Method for improving ferroelectric material apparent deflection electrical effects
CN109485410A